The future of osteoarthritis therapeutics: targeted pharmacological therapy - Mobasheri, Ali (Springer, 2013)
Osteoarthritis (OA) is one of the most common forms of degenerative joint disease and a major cause of pain and disability affecting the aging population. It is estimated that more than 20 million Americans and 35 to 40 million Europeans suffer from OA. Analgesics and non-steroidal anti-inflammatory drugs (NSAIDs) are the only therapeutic treatment options for OA. Effective pharmacotherapy for OA, capable of restoring the original structure and function of damaged cartilage and other synovial tissue, is urgently needed, and research into such disease-modifying osteoarthritis drugs (DMOADs) is in progress. This is the first of three reviews focusing on OA therapeutics. This paper provides an overview of current research into potential structure-modifying drugs and more appropriately targeted pharmacological therapy. The challenges and opportunities in this area of research and development are reviewed, covering the most up-to-date initiatives, trends, and topics.